The Metaverse : innovations and generative AI - Jauhiainen, Jussi S. (KeAi Communications, 2025)
Today, the Metaverse consists of various platforms, including digital twins of the physical world as well as virtual and blended digital-material environments that offer immersive experiences for individual users. By going beyond solely physical or virtual realms, these platforms unlock new possibilities for exploration, experimentation, and interaction. This makes it possible to transcend the limitations of innovation processes confined to physical locations, so the Metaverse is thus poised to drive groundbreaking innovations. This article explores the Metaverse as an innovation platform, its opportunities and challenges, including the role of generative AI in it. It discusses how the Metaverse, as a collaboration, creativity, and technological platform, supports innovation potential. By embracing the possibilities and challenges offered by the Metaverse and leveraging the capabilities of generative AI within it, a future in which individuals can truly explore novel synergies between the physical and digital realms, thriving various kinds of innovations. It is crucial to achieve holistic sustainability impacts both within the Metaverse innovation platform and as its outputs.